2016
DOI: 10.1186/s12864-016-3308-8
|View full text |Cite
|
Sign up to set email alerts
|

A transcriptome-based model of central memory CD4 T cell death in HIV infection

Abstract: BackgroundHuman central memory CD4 T cells are characterized by their capacity of proliferation and differentiation into effector memory CD4 T cells. Homeostasis of central memory CD4 T cells is considered a key factor sustaining the asymptomatic stage of Human Immunodeficiency Virus type 1 (HIV-1) infection, while progression to acquired immunodeficiency syndrome is imputed to central memory CD4 T cells homeostatic failure. We investigated if central memory CD4 T cells from patients with HIV-1 infection have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 110 publications
(137 reference statements)
2
14
0
Order By: Relevance
“…Previous studies have investigated changes in the global transcriptome of HIV-1 infected T-cells, B-cells, macrophages and the whole brain. In these studies, functional annotation of DEGs revealed HIV-1 adversely affects the TCA cycle, TGF-β signaling, reductive carboxylate cycle, cytokine-cytokine receptor interaction, cell cycle, DNA repair, apoptosis, immune response pathways and JAK-STAT signaling in PBMCs, CD4+ T cells and monocytes 22 , 47 . RNA-sequencing of HIV-1 infected monocytes and gene ontology analyses uncovered some of the HIV-1 infection specific effects on gene expression and chromatin remodeling 23 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have investigated changes in the global transcriptome of HIV-1 infected T-cells, B-cells, macrophages and the whole brain. In these studies, functional annotation of DEGs revealed HIV-1 adversely affects the TCA cycle, TGF-β signaling, reductive carboxylate cycle, cytokine-cytokine receptor interaction, cell cycle, DNA repair, apoptosis, immune response pathways and JAK-STAT signaling in PBMCs, CD4+ T cells and monocytes 22 , 47 . RNA-sequencing of HIV-1 infected monocytes and gene ontology analyses uncovered some of the HIV-1 infection specific effects on gene expression and chromatin remodeling 23 .…”
Section: Discussionmentioning
confidence: 99%
“…HIV-1-mediated changes in the transcriptome of HIV infected cells and tissues revealed widespread alterations in cellular pathways crucial for survival and functioning as well as processes that promote HIV-1 replication. Deep RNA sequencing of CD4+, CD8+ and CD14+ T-cells from PLWH demonstrated HIV-1-mediated changes in the transcriptome of these cells affecting metabolic, cell cycle and lipid profile pathways 21 , 22 . In addition, in HIV-1 infected macrophages, DNA and chromatin alterations have been reported 23 .…”
Section: Introductionmentioning
confidence: 99%
“…To this end, we downloaded a set of T cell microarray data (accession no. GSE73968 ) ( 45 ) from the GEO database ( https://www.ncbi.nlm.nih.gov/geo/ ). The expression level for each gene was further averaged by three replicates.…”
Section: Methodsmentioning
confidence: 99%
“…CD38 overexpression in HIV infection could translate in reduced NAD concentration in plasma and/or in T cell cytoplasm, increasing NAD flow from cytoplasm, and surpassing the cell’s capacity to maintain its NAD levels. In consonance with a possible NAD scavenging pressure on intracellular NAD pools, we have found overexpression of nicotinamide phosphoribosyl transferase mRNA (NAMPT), the rate limiting enzyme of the salvage pathway of NAD synthesis) in central memory CD4 T cells from persons living with HIV, [84] which might be compensating NAD removal due to CD38 overexpression. In this way, increased presence of CD38 with an extracellular active site might decrease cytoplasmic NAD concentration.…”
Section: Evidence Supporting Cd38-mediated Pathogenesis In Hiv Diseasementioning
confidence: 95%